Does Job Satisfaction Play a Mediator Role From Transformational Leadership and Organizational Culture to Organizational Citizenship Behavior - Safari, Luthfi Aulia; Aima, M Havidz; Hazrati Havidz, Ikramina Larasati (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to analyze the effect of transformational leadership and organizational culture on organizational citizenship behavior through job satisfaction as a mediating variable. Employees of bank employees belonging to KBMI 4 is the population of this study, namely Mandiri bank, BCA, BRI, and BNI. Structural Equation Model-Partial Least Square (SEM-PLS) is used in this research. The results found that Transformational Leadership and Organizational Culture has a positive and significant effect on Job Satisfaction, Transformational Leadership had no effect on Organizational Citizenship Behavior, Organizational Culture and Job Satisfaction has a positive and significant effect on Organizational Citizenship Behavior, Transformational Leadership, and Organizational Culture simultaneously effect on Job Satisfaction, Transformational Leadership and Organizational Culture simultaneously effect on Organizational Citizenship Behavior, Job Satisfaction did not mediate the influence of Transformational Leadership and Organizational Culture on Organizational Citizenship Behavior.